Effects of Gadolinium-Based Contrast Agents on Thyroid Hormone Receptor Action and Thyroid Hormone-Induced Cerebellar Purkinje Cell Morphogenesis - Ariyani, Winda; Iwasaki, Toshiharu; Miyazaki, Wataru; Khongorzul, Erdene; Nakajima, Takahito; Kameo, Satomi; Koyama, Hiroshi; Tsushima, Yoshito; Koibuchi, Noriyuki (Frontiers in Endocrinology, 2016)
Gadolinium (Gd)-based contrast agents (GBCAs) are used in diagnostic imaging to enhance the quality of magnetic resonance imaging or angiography. After intravenous injection, GBCAs can accumulate in the brain. Thyroid hormones (THs) are critical to the development and functional maintenance of the central nervous system. TH actions in brain are mainly exerted through nuclear TH receptors (TRs). We examined the effects of GBCAs on TR-mediated transcription in CV-1 cells using transient transfection-based reporter assay and thyroid hormone-mediated cerebellar Purkinje cell morphogenesis in primary culture. We also measured the cellular accumulation and viability of Gd after representative GBCA treatments in cultured CV-1 cells. Both linear (Gd-diethylene triamine pentaacetic acid-bis methyl acid, Gd-DTPA-BMA) and macrocyclic (Gd-tetraazacyclododecane tetraacetic acid, Gd-DOTA) GBCAs were accumulated without inducing cell death in CV-1 cells. In contrast, Gd chloride (GdCl3) treatment induced approximately 100 times higher Gd accumulation and significantly reduced the number of cells. Low doses of Gd-DTPA-BMA (10−8–10−6 M) augmented TR-mediated transcription, but the transcription was suppressed at higher dose (10−5 – 10−4 M), with decreased β-galactosidase activity indicating cellular toxicity. TR-mediated transcription was not altered by Gd-DOTA or GdCl3, but the latter induced a significant reduction in β-galactosidase activity at high doses, indicating cellular toxicity. In cerebellar cultures, the dendrite arborization of Purkinje cells induced by 10-9 M T4 was augmented by low-dose Gd-DTPA-BMA (10−7 M) but was suppressed by higher dose (10−5 M). Such augmentation by low-dose Gd-DTPA-BMA was not observed with 10-9 M T3, probably because of the greater dendrite arborization by T3; however, the arborization by T3 was suppressed by a higher dose of Gd-DTPA-BMA (10-5 M) as seen in T4 treatment. The effect of Gd-DOTA on dendrite arborization was much weaker than that of the other compounds. These results indicate that exposure to specific GBCAs may, at least in part, cause toxic effects in the brain by disrupting the action of THs on TRs. The toxic effects of GBCAs may depend on the chemical structure of GBCA and the dose. Thus, it is very important to choose appropriate GBCAs for imaging to prevent adverse side effects.